In Vivo Expression of Reprogramming Factors Increases Hippocampal Neurogenesis and Synaptic Plasticity in Chronic Hypoxic-Ischemic Brain Injury - Cho, Sung-Rae; Kim, MinGi; Yu, Ji Hea; Wi, Soohyun (Journal of neural transplantation & plasticity, 2016)
Neurogenesis and synaptic plasticity can be stimulated in vivo in the brain. In this study, we hypothesized that in vivo expression of reprogramming factors such as Klf4, Sox2, Oct4, and c-Myc would facilitate endogenous neurogenesis and functional recovery. CD-1® mice were induced at 1 week of age by unilaterally carotid artery ligation and exposure to hypoxia. At 6 weeks of age, mice were injected GFP only or both four reprogramming factors and GFP into lateral ventricle. Passive avoidance task and open field test were performed to evaluate neurobehavioral function. Neurogenesis and synaptic activity in the hippocampus were evaluated using immunohistochemistry, qRT-PCR, and/or western blot analyses. Whereas BrdU+GFAP+ cells in the subgranular zone of the hippocampus were not significantly different, the numbers of BrdU+βIII-tubulin+ and BrdU+NeuN+ cells were significantly higher in treatment group than control group. Expressions of synaptophysin and PSD-95 were also higher in treatment group than control group. Importantly, passive avoidance task and open field test showed improvement in long-term memory and decreased anxiety in treatment group. In conclusion, in vivo expression of reprogramming factors improved behavioral functions in chronic hypoxic-ischemic brain injury. The mechanisms underlying these repair processes included endogenous neurogenesis and synaptic plasticity in the hippocampus.